Asuhan Kebidanan Ibu Hamil dengan Abortus Imminens Di Rumah Sakit Amelia Kabupaten Kediri - Lina Ratnawati; Winda Ayu Setiyorini (Gayaku Publisher, 2023)
Imminent abortion is a pregnancy complication that is often encountered and causes serious emotional burdens, occurs in one in five cases, and increases the risk of miscarriage or incomplete abortion. The purpose of this study was to provide midwifery care to mothers with Abortion Imminent at Amelia Hospital, Kediri Regency. The method used is a case study. The sample in this study is a single unit, namely Ny